2006
DOI: 10.1002/bit.21012
|View full text |Cite
|
Sign up to set email alerts
|

Fed-batch mode in shake flasks by slow-release technique

Abstract: Most industrial production processes are performed in fed-batch operational mode. In contrast, the screenings for microbial production strains are run in batch mode which results in completely different physiological conditions than relevant for production conditions. This may lead to wrong selections of strains. Silicone elastomer discs containing glucose crystals were developed to realize fed-batch fermentation in shake flasks. No other device for feeding was required. Glucose was fed in this way to Hansenul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
116
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(121 citation statements)
references
References 62 publications
5
116
0
Order By: Relevance
“…Scheidle et al (2009) and Stöckmann et al (2009) proved the thesis discussed above by demonstrating that the screening result markedly depends on the cultivation strategy used. The authors performed screenings of hundreds of Hansenula polymorpha clones under fed-batch conditions, feeding glucose by applying a polymer-based controlled-release system (Jeude et al, 2006) in 96-well deepwell MTP. By comparing these screenings to conventional screenings in batch mode, they clearly showed that fed-batch screenings yielded completely different results with respect to the best-producing clones.…”
Section: Introductionmentioning
confidence: 99%
“…Scheidle et al (2009) and Stöckmann et al (2009) proved the thesis discussed above by demonstrating that the screening result markedly depends on the cultivation strategy used. The authors performed screenings of hundreds of Hansenula polymorpha clones under fed-batch conditions, feeding glucose by applying a polymer-based controlled-release system (Jeude et al, 2006) in 96-well deepwell MTP. By comparing these screenings to conventional screenings in batch mode, they clearly showed that fed-batch screenings yielded completely different results with respect to the best-producing clones.…”
Section: Introductionmentioning
confidence: 99%
“…This could not be met with previous soft sensors used by us (Warth et al, 2010;Gustavsson and Mandenius., 2013) where delay times of up to 20 min seriously hampered the controllability of the system. An alternative setup would have been to extend the gas analyser with on-line measurement of O 2 , hence allowing monitoring of oxygen uptake rate (OUR) as well as respiratory quotient (RQ) by combining CO 2 and O 2 measurements (Levisauskas et al, 1996;Jeude et al, 2006). However, the on-line measurability of CO 2 with existing CO 2 sensors seems better than with available O 2 analyser alternatives.…”
Section: Soft Sensor Structure and Its Performancementioning
confidence: 98%
“…Use of hydrogels has been reported for controlled delivery of growth factors to animal cells 64 . Continuous delivery of glucose and sodium carbonate using silicone elastomer discs has been reported for in situ release to microbial systems over a period of one or two days to achieve nutrient feeding and pH control respectively 65,66 . Unlike microbial cultures which run for short durations of 24-48 h, animal cells in fed batch are cultured for 7-15 days.…”
Section: Strategies For High and Medium Throughput Clone Screeningmentioning
confidence: 99%